Efektivitas Model Pembelajaran Tutor Sebaya Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran IPS - Dahliana, Dahliana; Okianna, Okianna; Barella, Yusawinur (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effectiveness of the peer tutor learning model on student learning outcomes in social studies subjects. The form of this research is pre-experiment design with research design one group pre-tets post-test. The subjects in this study were class VII F in Pontianak, totaling 29 people. Data collection techniques in this study were direct observation techniques, measurement techniques, and documentary study techniques. The data collection tool is in the form of observation sheets or lists check note sheets and learning outcomes tests in the form ofpre-test and post test. Based on the analysis of the data studied, the normality results state that the residual values ​​are normally distributed with a significant value of 0.200,> 0.05. While the results of the hypothesis test stated that Ho was rejected and Ha was accepted. Based on the significant value of the results pre-test and post-test, a value of 0.000 means it is smaller than 0.05. From testing the hypothesis it can be concluded that there is effectiveness in using the peer tutoring model on the learning outcomes of class VII students in Pontianak, and there are differences in the learning outcomes of students before and after using the peer tutoring model with an average scorepre-test 64,14 and post-test 76.90. From the calculation results effect size the results obtained were 0.883 in the high category. This means that the peer tutor learning model has a major influence in improving student learning outcomes in social studies class VII F in Pontianak.